FAKTOR-FAKTOR YANG MEMENGARUHI LOYALITAS NASABAH PADA BPR ARTHA PRIMA PERKASA DI KOTA BATAM - Kusniati, Kusniati; Saputra, Asron (FEB Universitas Sam Ratulangi Manado, 2020)
Bank Perkreditan Rakyat (BPR) is a financial establishment that aims to provide services to its customers. In this case, the quality of services provided by BPR Artha Prima Perkasa to customers is stiII reIativeIy Iow, causing the level of customer loyalty to be low. Customer satisfaction is also one of the factors that causes the levei of customer loyalty to be low. In this study aims to determine the effect of service quality and customer satisfaction on customer loyalty and also aims to increase customer loyalty. This study uses BPR Artha Prima Perkasa customers as respondents in filling out the questionnaire as many as 170 customers. The tests used in this research are data quality test, classic assumption test, influence test and hypothesis test. From the results of this study found the influence of service quality on customer Ioyalty is a significant effect where the significant value is 0,001 < 0,05 and thitung is greater than ttable (3,245 > 1,653), the effect of customer satisfaction on customer loyalty also has a significant effect where the significant value is 0,000 < 0, 05 and thitung is greater than table (3,742 > 1,653) and simultaneously service quality and customer satisfaction significantly influence customer Ioyalty where the significance value is 0,000 < 0,05 and fhitung is greater than ftabel (23,982> 3.05). While the value of R2 is 22,3% this study is influenced by variables of service quality and customer satisfaction, while the remaining 77,7% is influenced by other variables not examined in this study.Â Keywords: Customer loyalty; Customer Satisfaction; Service Quality.